Pencegah Komplikasi Akibat Peningkatan Tekanan Darah dengan Pola Hidup Sehat - Darussalam, Miftafu; Iskandar, Rahayu; Riyadi, Sujono (JOURNAL OF PHILANTHROPY: The Journal of Community Service, 2023)
Hypertension is one of the main risk factors for cardiovascular disease. Continuously high blood pressure conditions will cause the heart to work harder, so this condition will result in damage to the blood vessels, heart, kidneys, brain, and eyes. To achieve an increase in public health status through comprehensive health care, joint efforts from all levels of society are urgently needed so that health status is more evenly distributed. For this reason, it is considered necessary to pay attention to high-risk groups, namely the elderly, who need special treatment. The results of the health status of the elderly in RW 08 Patang Puluhan Village found that many older people did not understand the complications of hypertension and how to prevent them, so counseling about hypertension was necessary. Thirty-one participants attended this service. The activity was held at the Pendopo of Sindurejan Village, Patangpuluhan. Community service, as an effort to realize the Tri Dharma of Higher Education, is expected to help health promotion programs and interest the elderly in early detection or control of hypertension so that if there are signs of disease symptoms, they can be detected earlier. In addition, this community service can be a means to increase knowledge about hypertension. Implementation of activities consists of three stages: preparation, implementation, and evaluation. The results of community service showed that the knowledge of the elderly before and after education increased knowledge, with the mean value for the pretest score being 69.35 and the mean value for the posttest score being 92.34. So there is an increase of 22.99. Based on the Paired T-Test statistical test, there is a significant difference between knowledge before and after being given counseling with a p-value of 0.000. Suggestions for further development of community service require assistance from the Puskesmas Wirobrajan so that the elderly can apply the knowledge that has been obtained optimally. For the role of elderly cadres, support is needed from various aspects, such as coordination with the Puskesmas in realizing a sustainable program through the Posyandu Lansia.